Integrated Smart Glass and Photovoltaic Module Prototype Application Considering User Comfort Orientation - Boyckin, Tahsin; Boynucgri, Ali Rifat; Gokcek, Tayfur; Erdinc, Ozan; Kiyak, Ismail (IEEE, 2024)
Currently, smart glass systems and building-integrated photovoltaic (BIPV) systems are offered as two separate technological products. In this study, a smart glass solar panel technology is developed for the buildings, in which these two modules are integrated. The proposed new structure consists of a 240 Wp PV panel that can be integrated into the building, and a controllable laminated smart glass panel. In addition to the BIPV applications, the film structure with controllable transparency makes the irradiation usable by the PV cells by reflecting irradiation that cannot be used by the PV cells, or passes through them without being absorbed. The proposed design is also grid-connected, and provides support when the energy generated exceeds the demand. Additionally, energy efficiency can be significantly increased via the energy management system by controlling the internal temperature of the nodes where the integrated smart glass structure is used. According to the test results, 5% more electricity has been generated compared to the conventional PV applications, besides increasing user comfort.
Keywords: Building-integrated photovoltaic system; energy efficiency; energy management system; smart glass panel; photovoltaic generation; FA ADE; PERFORMANCE; SYSTEMS; WINDOW; Energy & Fuels; Engineering